National Independent Fiscal Institutions Need to Be Stronger to Perform Effectively - Daniel Daianu (Intereconomics, 2024)
In April 2023, the European Commission issued a directive proposal on EU economic governance reform. The Council cut some tasks of Independent Fiscal Institutions (IFIs) that were in the Commission directive proposal; whether this cutting is justified is an open question. Early this year, the Council and the Parliament reached a provisional agreement on the proposed reform of the EU economic governance framework. The vision of the Commission that would involve IFIs in the assessment of fiscal-structural plans is not groundless. But structural reforms and investment analysis demand expertise that hardly exists in most national IFIs, and their involvement in policy design could be perceived as a technocratic inroad into democratic decision-making. In order to play a more significant and effective role, national IFIs need adequate resources and enhanced analytical capacity; their activity depends heavily on the policy design of the EU economic governance. National IFIs should view their role from a macroprudential perspective, too. The role of IFIs should not go beyond what most of them can deliver effectively, so that their status and reputation are not harmed.
Keywords: E62; F15; H61; 330